(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article presents the absorption capacity and composition of absorbed cations of rice-growing meadow-swamp soils . It was noted that in the continuous planting system, a decrease in the amount of Ca2+ along the layer and the predominance of Mg2+ lead to a disruption of the element balance. This is accompanied by structural degradation, competition between cations, and negative impacts on plant physiology. It is explained that the amount of absorbed cations in these soils is one of the main factors determining their physicochemical properties, nutritional capacity, and melioration status.